TO THE QUESTION ABOUT THE CONSIDERATION OF THE PECULIARITIES OF SPEECH DEVELOPMENT OF BILINGUAL CHILDREN IN EDUCATIONAL PROCESS - Irina Istomina (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the nature of bilingualism and the peculiarities of the speech development of bilingual children. There are represented a pedagogical conditions conducive to the effective organization of educational process in bilingual children. These conditions are associated with the peculiarities of speech development in bilinguals and include consideration of specific interaction of teacher and child bilingual, individualization, inclusion, and multicultural approach in it training and education, age-appropriate and organizational-methodical support of educational process.